2009
DOI: 10.1371/journal.pone.0006189
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stimulates Adipogenesis through the Akt-TSC2-mTORC1 Pathway

Abstract: BackgroundThe signaling pathways imposing hormonal control over adipocyte differentiation are poorly understood. While insulin and Akt signaling have been found previously to be essential for adipogenesis, the relative importance of their many downstream branches have not been defined. One direct substrate that is inhibited by Akt-mediated phosphorylation is the tuberous sclerosis complex 2 (TSC2) protein, which associates with TSC1 and acts as a critical negative regulator of the mammalian target of rapamycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
287
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(308 citation statements)
references
References 77 publications
16
287
1
4
Order By: Relevance
“…Increased de novo lipid synthesis is an important feature of cancer cells and it is suggested that induction of lipid metabolism by SREBP-1c promotes cancer progression by providing lipids required for membranes. mTORC1 has been shown to increase PPARg expression and then to promote adipogenesis (28). It has also been suggested that mTORC1 increases the activity of lipin 1, which is a phosphatidic acid phosphatase promoting triglyceride synthesis and enhancing the PPARg adipogenic activity (29).…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…Increased de novo lipid synthesis is an important feature of cancer cells and it is suggested that induction of lipid metabolism by SREBP-1c promotes cancer progression by providing lipids required for membranes. mTORC1 has been shown to increase PPARg expression and then to promote adipogenesis (28). It has also been suggested that mTORC1 increases the activity of lipin 1, which is a phosphatidic acid phosphatase promoting triglyceride synthesis and enhancing the PPARg adipogenic activity (29).…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…102,103 Hyperinsulinemia may be capable of inducing the adipogenesis of cells within the marrow stem cell niche through a signaling cascade involving PKB and mTOR, culminating with activation of C/EBPa and PPARg. 104 Conversely, hypoinsulinemia, a hallmark of type 1 diabetes and an eventual occurrence following b-cell failure in type 2 diabetics, may also indirectly lead to enhanced adipogenesis. Insulin receptor knockout mice display a 2-fold upregulation of the IGF-1 receptor through a yet unknown mechanism.…”
Section: Hyper-and Hypo-insulinemiamentioning
confidence: 99%
“…This may be explained by the relatively moderate weight gain observed after 6 months of insulin therapy, which was probably too small to affect adipocyte cell size. It may also be envisioned that insulin induces the differentiation of new adipocytes [15] and thereby increases storage capacity without any change in adipocyte size.…”
Section: Discussionmentioning
confidence: 99%